2001
DOI: 10.1111/j.1365-2958.2001.02314.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal insertion and excision of a 30 kb unstable genetic element is responsible for phase variation of lipopolysaccharide and other virulence determinants in Legionella pneumophila

Abstract: We recently described the phase‐variable expression of a virulence‐associated lipopolysaccharide (LPS) epitope in Legionella pneumophila. In this study, the molecular mechanism for phase variation was investigated. We identified a 30 kb unstable genetic element as the molecular origin for LPS phase variation. Thirty putative genes were encoded on the 30 kb sequence, organized in two putative opposite transcription units. Some of the open reading frames (ORFs) shared homologies with bacteriophage genes, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 58 publications
2
52
0
Order By: Relevance
“…Notably, the lvh region of L. pneumophila Paris is encoded in a 36-kb region that is either integrated in the chromosome or excised as a multicopy plasmid (data not shown). This pattern is similar to that described for the 30-kb unstable element of strain Olda, which is possibly derived from phage and is involved in phase variation 38 . The lvh region has a G+C content (43%) that differs from that of the rest of the chromosome (38%), and it contains some phage-related genes, suggesting a possible phage origin.…”
Section: A R T I C L E Ssupporting
confidence: 67%
“…Notably, the lvh region of L. pneumophila Paris is encoded in a 36-kb region that is either integrated in the chromosome or excised as a multicopy plasmid (data not shown). This pattern is similar to that described for the 30-kb unstable element of strain Olda, which is possibly derived from phage and is involved in phase variation 38 . The lvh region has a G+C content (43%) that differs from that of the rest of the chromosome (38%), and it contains some phage-related genes, suggesting a possible phage origin.…”
Section: A R T I C L E Ssupporting
confidence: 67%
“…Furthermore, plasmid excision and integration appear to constitute a particular mechanism of genome plasticity in Legionella. For example, the Lvh T4ASS can be present in an integrated and excised form Chien et al 2004;Doleans et al 2006), similar to a 30-kb element specific for strain Olda associated with loss of virulence (Luneberg et al 2001) and the two recently reported mobile elements carrying T4ASS in strain Corby (Glöckner et al 2007). In addition, our results suggest that the 130-kb plasmid of strain Paris may integrate into the genome associated with loss of the genes necessary for plasmid replication.…”
Section: Discussionmentioning
confidence: 99%
“…In the strains where pLpp is present only in part, a 85-kb region carrying the twocomponent system lrpR-lskS implicated in the virulence of L. longbeachae (Doyle and Heuzenroeder 2002) was present, whereas the 45-kb region (plpp0001-plpp0045) bordered by an integrase (plpp0140) and coding a homolog of CsrA and for plasmid-related functions like partition and replication proteins and the conjugation transfer proteins Tra, is missing. As integration and circularization of plasmids have been shown for Legionella (Luneberg et al 2001;Doleans et al 2006), it is tempting to assume that parts of pLpp may, under certain conditions, integrate into the chromosome. …”
Section: Horizontal Gene Transfer Of Mobile Genetic Elements Among Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the frequency of excision and insertion of IS492 directly regulates the production of these molecules, which are important in biofilm formation. Similarly, the formation of a specific lipopolysaccharide in Legionella pneumophila depends on the presence of a 30-kb unstable genetic element in its chromosome (413). This element probably originates from a phage and can excise as a replicating plasmid, consequently stopping its host's production of lipopolysaccharide.…”
Section: Site-specific Recombinationmentioning
confidence: 99%